2019
DOI: 10.1002/cctc.201801511
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxygen Reduction Activity on Carbon Supported Pd Nanoparticles Via SiO2

Abstract: To improve Pd‐based catalysts activity and stability is still challenge although Pd‐based catalysts have attracted attention for oxygen reduction reaction (ORR) during recent years. In this study, we have prepared supported Pd on SiO2, in which conductive carbon was used by coprecipitation method Pd/SiO2@C or physically mixed Pd/SiO2.Pd/SiO2@C (10 wt%) owned more outstanding catalytic activity, preferable durability, and stronger methanol tolerance capability in alkaline solution for ORR, which compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The lower FE in the test was due to the side reactions, including the hydrogen evolution reaction and oxygen reduction reaction to produce H 2 O. 47 All results with no quadratic function relationship were in the predictable concentration trend range, providing an excellent reference value for the actual production of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 87%
“…The lower FE in the test was due to the side reactions, including the hydrogen evolution reaction and oxygen reduction reaction to produce H 2 O. 47 All results with no quadratic function relationship were in the predictable concentration trend range, providing an excellent reference value for the actual production of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 87%
“…However, interestingly, two distinct decreasing trends were observed at specific current density ranges, approximately between 80 and 120 and 130–140 mA/cm 2 , respectively. It was proposed that the first decreasing trend was attributed to the competition of the H 2 O 2 reduction reaction, as reported in previous studies. , The second decreasing trend was proposed to be linked to the occurrence of the 4e – ORR reaction, leading to the generation of H 2 O . The analysis of current densities (Figure d–f) revealed that the optimum current density for the electrocatalytic production of H 2 O 2 using the COPN-3 catalyst was 130 mA/cm 2 across various pH environments.…”
Section: Resultsmentioning
confidence: 99%
“…57,58 The second decreasing trend was proposed to be linked to the occurrence of the 4e − ORR reaction, leading to the generation of H 2 O. 59 The analysis of current densities (Figure 4d−f) revealed that the optimum current density for the electrocatalytic production of H 2 O 2 using the COPN-3 catalyst was 130 mA/cm 2 across various pH environments. At this optimized current density, the COPN-3 catalyst demonstrated remarkable performance, yielding high H 2 O 2 concentrations over 120 min.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13 Alternatively, it has long been predicted that metal to substrate charge-transfer interactions (MSI) can be used for regulating the metal-oxygen bond-strengths [22][23][24] and was demonstrated experimentally using various substrates such as sp 2 carbon derivatives recently for improved ORR activity. 25,26 The benefits of using graphene as a substrate include two additional aspects i.e. the defects provide anchoring points to the metal to offer higher stability and prohibits the Ostwald ripening of the nanoparticles during growth to improve catalyst surface-area.…”
Section: Introductionmentioning
confidence: 99%